Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria (Forest Ecology and Management, 2013)
The current trend of declining epiphytic richness caused by human activities (forest fragmentation, log- ging, agriculture, and livestock grazing) and the greater efforts required to sample and identify the most inconspicuous species have necessitated the use of indicators of the species richness. In this study, we examined the potential of predicting epiphytic lichen richness based on the richness of a single taxon (fam- ily) of the most conspicuous lichens (macrolichens) in Mediterranean woodlands. Since our working hypothesis is that the richness of some conspicuous elements is tightly connected with the total richness, we expect this connection is maintained even after composition shifts (for instance composition changes between coniferous and oak forests). In order to control the large set of confounding factors at macro- and microclimate scales our present study was conducted in 504 forest stands, which represented awide range of Mediterranean climates, management intensity levels, canopy cover types, and tree sizes. The presence/ absence of epiphytic lichens were determined in 7560 trees, which were dominated by coniferous (Pinus nigra and P. sylvestris) and oak (Quercus ilex ssp. ballota, Q. faginea, and Q. pyrenaica) species. In oak forests, the increased richness of Collemataceae and the complex known as ‘‘rest of Peltigerales’’ was followed by an increase in the overall epiphytic richness, whereas there was a strong positive correlation between Par- meliaceae and total epiphytic richness in coniferous forests. In both cases, the richness of these predictors increased in well-preserved forest stands with dense canopies. Thus, we propose the potential use of Par- meliaceae (for coniferous forests) and the Collemataceae and the ‘‘rest of Peltigerales’’ (for oak forests) as indicators in the Mediterranean region because they have a cosmopolitan distribution, grow in a wide range of environmental conditions, and are correlated with changes in the epiphytic richness caused by for- est disturbances. ?
From Duplicate 2 ( Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria )From Duplicate 2 ( Estimating epiphytic lichen richness by single families in Mediterranean forests - Aragón, Gregorio; Belinchón, Rocío; Martínez, Isabel; Prieto, Maria )
Keywords: epiphytic lichens; Forest structure; Indicator species; Mediterranean; Species richness

Increasing Drought Sensitivity and Decline of Atlas Cedar (Cedrus atlantica) in the Moroccan Middle Atlas Forests - Linares, Juan C; Taiqui, Lahcen; Julio Camarero, Jesus (FORESTS, 2011)
An understanding of the interactions between climate change and forest structure on tree growth are needed for decision making in forest conservation and management. In this paper, we investigated the relative contribution of tree features and stand structure on Atlas cedar (Cedrus atlantica) radial growth in forests that have experienced heavy grazing and logging in the past. Dendrochronological methods were applied to quantify patterns in basal-area increment and drought sensitivity of Atlas cedar in the Middle Atlas, northern Morocco. We estimated the tree-to-tree competition intensity and quantified the structure in Atlas cedar stands with contrasting tree density, age, and decline symptoms. The relative contribution of tree age and size and stand structure to Atlas cedar growth decline was estimated by variance partitioning using partial-redundancy analyses. Recurrent drought events and temperature increases have been identified from local climate records since the 1970s. We detected consistent growth declines and increased drought sensitivity in Atlas cedar across all sites since the early 1980s. Specifically, we determined that previous growth rates and tree age were the strongest tree features, while Quercus rotundifolia basal area was the strongest stand structure measure related to Atlas cedar decline. As a result, we suggest that Atlas cedar forests that have experienced severe drought in combination with grazing and logging may be in the process of shifting dominance toward more drought-tolerant species such as Q. rotundifolia.
Keywords: basal area increment; Cedrus atlantica; climate change; Dendroecology; Drought; Forest structure; partial redundancy analysis

Determination of the natural mortality age of an holm oak ( Quercus ilex L.) stand in Corsica (Mediterranean Island) - Panaiotis, C; Carcaillet, C; M'Hamedi, M (Acta Oecologica, 1997)
Determination of old forest stand age and forestry history is problematic due to the difficulties which arise in obtaining core samples from trees. In the present paper, the natural mortality age and forestry history of a Corsican holm oak stand are estimated using the methods described below. Firstly, the correlation between stem age estimated from healthy stump counts in fellings and stem diameter is determined using a second order polynomial equation. Secondly, the distribution of stand diameter classes is analyzed by the BHATTACHARYA (1967) method. This method allows the identifica- tion of cohorts as well as the estimation of cohort mean diameters and theoretical tree count numbers. Using cohort mean diameters, we are able to estimate their age and discuss stand forestry history. Finally, the analysis of thirty broken stumps originating from senescent holm oak natural falls, is used to determine the mean natural mortality age of trees bused on their mean diameter. This natural mor- tality is estimated to occur at 170 -+ 46 years of age. The causes of holm oak mortality and the capacity of old stumps to renew the ecosystem are discussed in order to contribute to the conservation and man- agement of these woodland communities.
Keywords: Corsica; Dendrochronology; Forest structure; mediterranean forest; natural mortality; old forest; Quercus ilex

Effect of site quality and thinning management on the structure of holm oak forests in northeast Spain - Gracia, M; RETANA, J (Ann. For. Sci., 1996)
In the holm oak forests of NE Spain, the variability of thinning intensity, together with the great heterogeneity of site quality, due to the rough topography of the region, gives rise to important structural differences among stands. In this paper, we analyze the effect of site quality and thinning management on the structural heterogeneity of holm oak stands at the end of the cutting cycle in different areas of the Montseny and Les Guilleries massifs (NE Spain). These two factors influence the main structural variables of the stands in various ways. Height was used as an indicator of site quality, because it was relatively unaffected by thinning management, while density and total number of stems per stool were strongly affected. Mean tree diameter reflected the effect of both site quality and thinning. The type of forest management was found to be the most important factor determining forest structure. Site quality was a constraint of stand development, contributing in poor stands, to increased differences due to thinning management.
Keywords: Forest structure; Holm oak; Ouercus ilex; site quality; thinning

CARACTERIZACION ESTRUCTURAL DE LOS ENCINARES DE CATALUÑA Marc - Gracia, Marc; Retana, Javier; Espelta, Josep Maria; Gené, Caries (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, a characterization of structure of holm-oak forests in the Northeastem Iberian Peninsula is proposed. The study is based on different features of these forests, both at the stand and at the individuallevel.
Keywords: Basal area; density of stems; Forest structure; holm-oak; Quercus ilex; size distri bu ti on

Structure, biomass and production of a resprouted holm-oak (Quercus ilex L.) forest in NE Spain - LLEDO, M J; Sánchez, J R; Bellot, J; Boronat, J (Plant Ecology, 1992)
When considered as a compartment of nutrients (biomass) and as a flux between compartments (pro- duction) vegetation plays an important role in the biogeochemical forest research that is carried out at the Prades research station in two adjacent catchments: L'Avic (51.6 ha) and La Teula (38.5 ha). The forest density at the Prades site, considering both the tree and shrub layers, is 9182 stems ha t, with 4527 stems ha i being the tree layer. The predominant species is Quercus ilex with Arbutus unedo and Phillyrea media less common. The structure of the population, estimated by grouping the numbers of the stems in classes of 2.5 cm, shows a distribution which conforms, in both catchments, to a negative exponential equation following the Yoda law. The distribution observed at different altitudes shows great heterogeneity, the number of stems of Q. ilex increases with altitude, from 4000 stems ha ~ at 800 m, to 14000 stems ha 1 at 1000 m of altitude. The upper and the lower parts of the watershed show dif- ferences in forest production that explain this variation. In this paper the influence of human activities and physical factors on the origin of this structure is discussed. The tree and shrub biomass was cal- culated by applying allometric regressions for the three predominant species and has been estimated as 113.2 t ha 1. The tree layer accounts for 92°o. Net production was calculated from annual increases (by differences between the 1981 and 1986 basal area measures) of the woody part and the litterfall. The above-ground net production was about 6.5 t ha 1 year 1, 95.4o0 of it being from trees and shrubs and only 4.6°0 from grasses.
Keywords: Forest structure; human activities; mediterranean forest; prades; Species distribution